A bottom-up strategy toward a flexible vanadium dioxide/silicon nitride composite film with infrared sensing performance. Issue 22 (2nd June 2020) - Ma, He; Wang, Yu; Fu, Yulan; Zhang, Xinping
Abstract : Traditional VO2 films grown on rigid substrates are inflexible, which limits their applications. In this work, we successfully prepared VO2 /silicon nitride composite films by a simple template method. Abstract : Vanadium dioxide (VO2 ) attracts great attention due to its well-known metal-to-insulator transition. However, traditional VO2 films grown on rigid substrates are inflexible, which limits their applications. In this work, we successfully prepared VO2 /silicon nitride (VO2 /SN) composite films by a simple template method. The VO2 /SN film shows high flexibility, strong infrared absorption, and drastic resistance change (>10 3 ) induced by the phase transition. The application of the VO2 /SN film is presented by infrared sensing, which shows a high responsivity (720 V W −1 ) and short response time (409 ms).